The GPR120 agonist TUG‐891 promotes metabolic health by stimulating mitochondrial respiration in brown fat. Issue 3 (17th January 2018) - Schilperoort, Maaike; van Dam, Andrea D; Hoeke, Geerte; Shabalina, Irina G; Okolo, Anthony; Hanyaloglu, Aylin C; Dib, Lea H; Mol, Isabel M; Caengprasath, Natarin; Chan, Yi‐Wah; Damak, Sami; Miller, Anne Reifel; et al.
Abstract: Brown adipose tissue (BAT) activation stimulates energy expenditure in human adults, which makes it an attractive target to combat obesity and related disorders. Recent studies demonstrated a role for G protein‐coupled receptor 120 (GPR120) in BAT thermogenesis. Here, we investigated the therapeutic potential of GPR120 agonism and addressed GPR120‐mediated signaling in BAT. We found that activation of GPR120 by the selective agonist TUG‐891 acutely increases fat oxidation and reduces body weight and fat mass in C57Bl/6J mice. These effects coincided with decreased brown adipocyte lipid content and increased nutrient uptake by BAT, confirming increased BAT activity. Consistent with these observations, GPR120 deficiency reduced expression of genes involved in nutrient handling in BAT. Stimulation of brown adipocytes in vitro with TUG‐891 acutely induced O2 consumption, through GPR120‐dependent and GPR120‐independent mechanisms. TUG‐891 not only stimulated GPR120 signaling resulting in intracellular calcium release, mitochondrial depolarization, and mitochondrial fission, but also activated UCP1. Collectively, these data suggest that activation of brown adipocytes with the GPR120 agonist TUG‐891 is a promising strategy to increase lipid combustion and reduce obesity. Synopsis: This study demonstrates that the GPR120 agonist TUG‐891 improves metabolic health by activation of brown fat. Mechanistically, TUG‐891 promotes respiration in brown adipocytes by stimulating GPR120‐dependent Ca 2+ release and mitochondrial fragmentation, thereby activating UCP1. The GPR120 agonist TUG‐891 acutely increases fat oxidation and decreases body weight and fat mass in mice. Beneficial metabolic effects of TUG‐891 are related to increased brown fat activity, reflected by an increased uptake of fatty acids by brown adipose tissue in vivo . TUG‐891 increases mitochondrial respiration in brown adipocytes in vitro, via both GPR120‐ dependent and ‐independent mechanisms. Abstract : This study demonstrates that the GPR120 agonist TUG‐891 improves metabolic health by activation of brown fat. Mechanistically, TUG‐891 promotes respiration in brown adipocytes by stimulating GPR120‐dependent Ca 2+ release and mitochondrial fragmentation, thereby activating UCP1.